(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Business to Business (B2B) requires a consultative selling which means understanding the client’s needs and building a trust relationship as part of business strategy. This approach is different than Business to Customer (B2C) marketing where goods and services are directly sold to end user or retailer. Due to promotion to digitalization in BRICS (Brazil, Russia, India, China & South Africa), there a renew approaches towards digital marketing and hence such strategies are developed. To restrict the scope of research, this study focuses on analyzing the B2B digital marketing strategies for Small and Medium Enterprises (SME) with respect to original equipment manufacturer (OEM) in automotive industry. This research explores the differences in the approaches followed for B2B marketing strategies and how effectively new technologies like Big Data, Business Analytics, Internet of Things (IoT), CRM, ERP, Social Media and Inbound Marketing are being used by SMEs.